A Selective Screening Strategy Performed in Pre-School Children and Siblings to Detect Familial Hypercholesterolemia - Alexandra Thajer; Margot Baumgartner; Anselm Jorda; Ulrike Hallwirth; Julia Lischka; Susanne Greber-Platzer (MDPI AG, 2022)
(1) Background: Familial hypercholesterolemia (FH), a most common genetic disorder, is underdiagnosed and untreated, especially in children. Individuals with heterozygous familial hypercholesterolemia mostly present without clinical symptoms and are not informed about their high risk for myocardial infarction. Early diagnosis and treatment can prevent premature atherosclerosis and cardiovascular events in patients with FH. The aim was to evaluate the detection rate of pre-school children with FH at school doctor visits in Vienna and, moreover, to examine the frequency of FH identified in the children's siblings by this type of screening. (2) Methods: The selective FH- screening was implemented at the school enrolment examinations in the public primary schools of Vienna. The study period included the school years starting in 2017 to 2020. FH was suspected if a questionnaire on hypercholesterolemia, or cardiovascular events in the family history or on the presence of xanthomas or xanthelasma, was positive. Subsequently, lipid testing was performed on pre-school children and their siblings and elevated lipid screening was defined as either positive by LDL-C ≥ 160 mg/dL and/or non-HDL-C ≥ 190 mg/dL or as borderline by LDL-C ≥ 130 mg/dL and/or non-HDL-C ≥ 160 mg/dL. (3) Results: 66,108 pre-school children participated in the school enrolment examination in 868 public elementary schools in Vienna. In 512 (4%) children, the questionnaire caused suspicion of FH. 344 families agreed their participation in the study. Out of 344 (52% male) tested pre-school children, 20 individuals (40% male) had elevated blood lipid levels with a mean LDL-C of 155 ± 29 mg/dL and a non-HDL-C of 180 ± 24 mg/dL. Out of 291 (44% male) tested siblings, 17 individuals (41% male) showed elevated lipids with a mean LDL-C of 144 ± 19 mg/dL, and a non-HDL-C of 174 ± 19 mg/dL. (4) Conclusions: Screening is the key for early diagnosis and treatment of FH. We have implemented a pre-school screening strategy in cooperation with school physicians. We could identify 20 pre-school children and 17 siblings with an elevated lipid screening test. Full implementation of FH-screening in the pre-school examination visits in Vienna would help to detect high-risk children.